Differentiation of arable field weed communities in the northern part of the Silesian Upland (S Poland). - Węgrzynek, Beata (Plant Breeding and Seed Science, 2010)
The purpose of this paper is to present the role of the selected species (i.e. associations character species, endangered as well as the most expansive weeds) in arable field communities in the area_of the Tarnowskie Góry Ridge and the Chełm, two mesoregions of the Silesian Upland (southern Poland). On the basis of 750 phytosociological relevés taken using the method of Braun-Blanquet (Braun-Blanquet 1964) between 1995 and 2009, eight weed associations as well as numerous rump communities were distinguished. Phytocoenoses without a significant contribution of the association character species comprised about 68% of the patches analysed in the cereal crop and about 12% of the communities established in the root plant crop. Very often the character species of cereal weed associations occurred sporadically or in small numbers. Some expansive weeds (e.g. Apera_spica-venti (L.) P. Beauv., Avena_fatua_L., A. vilis Wallr., Chenopodium album L., Echinochloa_crus-galli (L.) P. Beauv., Elymus repens L., Galinsoga_ciliata_(Raf.) S. F. Blake, G. parviflora_Cav.) played an important role in the communities analysed. The vanishing of some weed species and the spread of others has resulted in the transformation of the composition and structure of the segetal communities. a_vast majority of rare and endangered weed species in the studied area_are considered to be very sensitive to modern agriculture methods, e.g. chemicalization, introduction of new crop cultivars, effective cleaning of seed materials, drainage etc. (Siciński 1998; Warcholińska_1998)...